18 x 14 = 252
252 = 2 x 126 = 3 x ... = 4 x ... = 6 x ... = 9 x 28 = 12 x 21.
This one I was looking for, because -12 + 21 = +9
So 18x^2 + 9x - 14 = 18x^2 + 21x - 12x - 14 = 3x(6x + 7) - 2(6x + 7) =
(3x - 2)(6x + 7) That's it, Theajadasammy.
Th
2006-12-03 23:16:20
·
answer #1
·
answered by Thermo 6
·
0⤊
0⤋
1. 18x^2 + 9x -14 = (3x - 2) (6x + 7)
2. 3x^2 + 32x -11 = (3x -1) (x + 11)
2006-12-04 05:10:03
·
answer #2
·
answered by little_bigb0y 3
·
0⤊
0⤋
Express 9x in terms of the factors of the product of 18*(-14),
i.e. 9x = -12x+21x. it can be seen that 21*(-12)=18*(-14).
Rewrire the above equation as
18x^2-12x+21x-14
6x(3x-2)+7(3x-2)
(By taking out common factors from the 1st two terms & the last two terms).
Now taking (3x-2) common from the 2 terms & writing the remaining terms with the corresponding sign.
(3x-2)(6x+7)
2006-12-04 06:34:09
·
answer #3
·
answered by raghunandan r 1
·
0⤊
0⤋
18 = 1-18 2-9 3-6
14 is 1-14 2-7
one will be negative -and the highher product will be +
(6x + 7 )(3x - 2 )
2006-12-04 05:07:42
·
answer #4
·
answered by tom4bucs 7
·
0⤊
0⤋
1)
18x^2 + 9x - 14
18x^2 + 21x - 12x - 14
3x(6x + 7) - 2(6x + 7)
(6x + 7)(3x - 2)
2006-12-04 05:36:03
·
answer #5
·
answered by quark_sa 2
·
0⤊
0⤋
The square rule, if your in year 11
2006-12-04 05:07:21
·
answer #6
·
answered by year 12 student 2
·
0⤊
0⤋
(3x -1) (x+11)
2006-12-04 05:09:12
·
answer #7
·
answered by nisum90 2
·
0⤊
0⤋
(3x-2)(6x+7)
2006-12-04 05:06:30
·
answer #8
·
answered by Ranna Renni 2
·
0⤊
0⤋
(3x-2)*(6x+7) sound 'bout right? âº
Doug
2006-12-04 05:14:51
·
answer #9
·
answered by doug_donaghue 7
·
0⤊
0⤋
(6x+7)(3x-2)
6x+7=0
6x=-7
x=-7/6
3x-2=0
3x=2
x=2/3
2006-12-04 05:06:56
·
answer #10
·
answered by tma 6
·
0⤊
0⤋